2005
DOI: 10.1002/smi.1043
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural, cognitive and emotional responses to SARS: differences between college students in Beijing and Suzhou

Abstract: This research was designed to explore the differences in behaviour, cognition and emotion between college students in Beijing and Suzhou, who were under different external stresses during the severe acute respiratory syndrome (SARS) prevalence time in China from 22 April to 23 June, 2003. A ‘Psychological responses questionnaire on SARS’ designed by the authors was filled out by subjects. A total of 268 valid cases were collected in Beijing through e‐mails or websites, and 397 valid copies were collected in Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…On the one hand, married people are concerned not only for their own health but also for the health of their spouse in a pandemic, indicating an approximately 2-fold higher prevalence in mental disorders ( 56 ). Also, negative emotions may spread across individuals in a context full of unknown fears ( 57 ). On the other hand, married individuals have more concerns about the health of their families than their single counterparts ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, married people are concerned not only for their own health but also for the health of their spouse in a pandemic, indicating an approximately 2-fold higher prevalence in mental disorders ( 56 ). Also, negative emotions may spread across individuals in a context full of unknown fears ( 57 ). On the other hand, married individuals have more concerns about the health of their families than their single counterparts ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such consequences are more likely to cause psychological stress. Other research on the stress caused by epidemic diseases has revealed that the perception of SARS played a mediatory role between stress caused by external sources and emotional and behavioral responses (Qian et al, 2005). Moreover, the current study also found that the 'unpreventable and incurable' group had a higher possibility of experiencing epidemic-related stress events (such as infection or suspected infection with COVID-19 in friends, relatives and families), as well as a higher possibility of susceptible factors (such as severe physical illness, poor physical health, a history of mental illness or a history of counseling), which means that all those who had encountered stress events or exhibited susceptible factors had higher stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a 4-week longitudinal study (Wang et al 2020b ) focusing on PTSD symptoms and psychological distress (n = 478) showed a significant decline in PTSD symptoms over time, though they remained above cut-off, while no significant changes were seen in depression, anxiety and stress levels. In other words, the psychological impact of Covid-19 may persist, as already seen in the case of the SARS pandemic in survivors (Mak et al 2009 ), in the general population (Yeung and Fung 2007 ), and in university students (Cheng and Cheung 2005 ; Qian et al 2005 ). Some evidence has also emerged regarding the protective factors, which include: living in urban areas; living with parents; having a steady family income (Cao et al 2020 ); moderate physical exercise (Zhang et al 2020 ); both secure and avoidant attachment styles (Moccia et al 2020 ); confidence in doctors; perceived likelihood of surviving and low risk of contracting Covid-19; and satisfaction with health information and personal precautionary measures (Wang et al 2020a ).…”
Section: Introductionmentioning
confidence: 89%